Oxidative DNA damage during sleep periods among nightshift workers. Issue 8 (15th June 2016) - Bhatti, Parveen; Mirick, Dana K; Randolph, Timothy W; Gong, Jicheng; Buchanan, Diana Taibi; Zhang, Junfeng (Jim); Davis, Scott
Abstract : Objectives: Oxidative DNA damage may be increased among nightshift workers because of suppression of melatonin, a cellular antioxidant, and/or inflammation related to sleep disruption. However, oxidative DNA damage has received limited attention in previous studies of nightshift work. Methods: From two previous cross-sectional studies, urine samples collected during a night sleep period for 217 dayshift workers and during day and night sleep (on their first day off) periods for 223 nightshift workers were assayed for 8-hydroxydeoxyguanosine (8-OH-dG), a marker of oxidative DNA damage, using high-performance liquid chromatography with electrochemical detection. Urinary measures of 6-sulfatoxymelatonin (aMT6s), a marker of circulating melatonin levels, and actigraphy-based sleep quality data were also available. Results: Nightshift workers during their day sleep periods excreted 83% (p=0.2) and 77% (p=0.03) of the 8-OH-dG that dayshift workers and they themselves, respectively, excreted during their night sleep periods. Among nightshift workers, higher aMT6s levels were associated with higher urinary 8-OH-dG levels, and an inverse U-shaped trend was observed between 8-OH-dG levels and sleep efficiency and sleep duration. Conclusions: Reduced excretion of 8-OH-dG among nightshift workers during day sleep may reflect reduced functioning of DNA repair machinery, which could potentially lead to increased cellular levels of oxidative DNA damage. Melatonin disruption among nightshift workers may be responsible for the observed effect, as melatonin is known to enhance repair of oxidative DNA damage. Quality of sleep may similarly impact DNA repair. Cellular levels of DNA damage will need to be evaluated in future studies to help interpret these findings.